Concentration–effect relationships with perampanel in patients with pharmacoresistant partial‐onset seizures. Issue 8 (17th June 2013) - Gidal, Barry E.; Ferry, Jim; Majid, Oneeb; Hussein, Ziad
Summary Purpose Although there is a general paucity of published pharmacokinetic (PK) data for new antiepileptic drugs (AEDs), PK analyses of pooled data from clinical studies of perampanel have recently been presented. We present PK/pharmacodynamic (PD) analyses of pooled data from phase III studies of perampanel describing efficacy and safety as a function of exposure, in order to determine whether a predictable concentration–effect relationship exists for perampanel efficacy and/or adverse events (AEs). The effects of concomitant enzyme‐inducing AEDs (EIAEDs) and non–enzyme‐inducing AEDs on the exposure, efficacy, and safety of perampanel are also considered. Methods Three multicenter, randomized, double‐blind, placebo‐controlled phase III studies investigated the efficacy and safety of perampanel 2–12 mg in patients with uncontrolled partial‐onset seizures despite prior therapy with two or more AEDs. From baseline onward, patients also received ongoing treatment with stable doses of one to three approved concomitant AEDs. AEs were monitored throughout the studies. Changes from baseline in seizure frequency and 50% responder rates were evaluated. Exposure to perampanel was predicted based on the actual (last) dose using a previously established PK model. A population PK/PD model for the relationship between perampanel exposure and seizure frequency was estimated using nonlinear mixed‐effect modeling with first‐order conditional estimation, whereas logistic analyses for responder rate and AEs were performed using SAS analysis software. Key Findings The PK/PD population included 1, 109 patients. Seizure frequency decreased linearly as predicted perampanel average steady‐state plasma concentrations increased. Concomitant EIAEDs (carbamazepine, oxcarbazepine, and phenytoin) reduced exposure to perampanel but had no effect on the slope of the PD model–predicted relationship between exposure and reduction in seizure frequency. The probability of patients achieving a response was predicted to increase as perampanel average plasma concentration at steady state increased. No demographic, AED, region, or study covariate had any effect on the probability of achieving a positive treatment response to perampanel or on the slope of the exposure–response curve. Across the phase III studies, there were reports of dizziness (32.9%), somnolence (21.7%), fatigue (13.9%), irritability (12.3%), gait disturbance (9.1%), weight increase (6.1%), dysarthria (4.5%), and euphoric mood (0.5%); the model‐predicted probability of these AEs increased significantly at higher exposure to perampanel (all p < 0.001). There was no effect of demographic variables or region on the probability of experiencing any of the AEs analyzed. Significance PK and PD analyses have played a pivotal role in the clinical development of perampanel as an adjunctive treatment for pharmacoresistant partial‐onset seizures. Phase III data suggest that a significant relationship exists between increases in perampanel plasma concentration (i.e., systemic exposure) and reductions in seizure frequency. In addition, increases in perampanel plasma concentration may potentially be associated with increases in AE rates. The model‐predicted concentration‐safety profile of perampanel does not appear to be affected by patient age, gender, or ethnicity. Although concomitant EIAEDs may influence perampanel PK, they do not appear to alter the relationship between perampanel plasma concentration and seizure frequency. Understanding these relationships between perampanel plasma concentration and clinical response will be valuable in utilizing this novel AED.